2012
DOI: 10.1590/s0103-50532012000200017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between GC-MS-SIM and GC-ECD for the determination of residues of organochlorine and organophosphorus pesticides in Brazilian citrus essential oils

Abstract: Óleos essenciais cítricos brasileiros (mandarina, laranja, limão, bergamota e tangerina) foram analisados a fim de determinar resíduos de pesticidas organoclorados (aldrin, clordano, dieldrin e dicofol) e organofosforados (clorpirifós metílico, dimetoato, metidationa e paration metílico). Um estudo comparativo entre cromatografia gasosa acoplada a espectrometria de massas em modo de monitoramento seletivo de íons (CG-EM-MSI) e cromatografia gasosa com detector por captura de elétrons (CG-DCE) foi realizado usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This LOD/LOQ is much higher than that reported for CPO, which was 0.005 μg ml −1 or 5 ppb (Muhamad et al, 2012). The higher LOD for the method developed by Muhamad et al 2012 is because of the higher sensitivity of the GC‐ECD for halogenated compound compared with GC‐SIM‐MS detector (Alves et al, 2012). As previously described, the FA matrix still remains after the liquid–liquid partitioning and SPE clean up.…”
Section: Resultsmentioning
confidence: 99%
“…This LOD/LOQ is much higher than that reported for CPO, which was 0.005 μg ml −1 or 5 ppb (Muhamad et al, 2012). The higher LOD for the method developed by Muhamad et al 2012 is because of the higher sensitivity of the GC‐ECD for halogenated compound compared with GC‐SIM‐MS detector (Alves et al, 2012). As previously described, the FA matrix still remains after the liquid–liquid partitioning and SPE clean up.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorpyrifos, dicofol, and methidathion were the most frequently found pesticide types in essential oils. Alves et al showed that six organochlorines and organophosphorus pesticide concentrations are between 26 and 43.5 mg/L in Brazilian citrus oil (Alves et al, 2012). Propiconazole and tebuconazole fungicides used to prevent fungus in peppermint, were detected in essential oil at 0.02 to 0.05 mg/L and 0.01 to 0.04 mg/kg, respectively (Garland et al, 1999).…”
Section: Biocidesmentioning
confidence: 99%
“…On the other hand, essential oils (EOs) are extracted from citrus peel and the concentration of lipophilic pesticides is much higher than that found in the fruit [28]. Pesticide residues in EOs are widely studied by different researchers who have found organochlorine [29] and organophosphorus residues [30] among others. A review of the presence and evolution of pesticides and plasticizers in Italian essential oils according the type of citrus EO was published by Saitta and his group in 2012 [31].…”
Section: Introductionmentioning
confidence: 99%